THE JURISPRUDENCE - BASIC CONCEPTS OF BEING A FORMAL AND CONSTITUTIONAL SOURCE OF LAW (I) - Emilian CIONGARU (Challenges of the Knowledge Society)
The jurisprudence could be characterised as being a combination of previous but also completed situations in fact, previous but also consumed facts, which have been materialised by legal sentences or guidance decisions given by courts and competent bodies, through which the solution to the problems of law tried, becomes binding for the other lower courts in all similar cases which will be tried, in order to ensure a uniform and unitary interpretation and enforcement of the law throughout the territory of the country. In order to be able to characterise jurisprudence in Romanian law, in the sense of choosing between being or not being a formal source of law, it is firstly necessary to analyse the system, the whole current legal framework, including as regards the organization of the judicial system and of the courts. Romanian national law is characterised through Roman Germanic law as being a procedural law in which the judicial activity is carried out on the basis of strict rules, as is that of the judge, who has the duty to receive and settle any claim within the competence of the courts, according to the law and no judge may refuse to judge on the grounds that the law does not provide, is unclear or incomplete and, in the case in which a case cannot be settled neither on the basis of the law nor of customary practices, and in the absence of the latter, nor on the basis of legal provisions for similar situations, it shall be judged on the basis of the general principles of law, having regard to all its circumstances and taking into account the requirements of equity.